Activities, substrate specificity, and genetic interactions of fission yeast Siw14, a cysteinyl-phosphatase-type inositol pyrophosphatase - Ana M. Sanchez; Beate Schwer; Nikolaus Jork; Henning J. Jessen; Stewart Shuman (mBio, 2023)
ABSTRACT Inositol pyrophosphate 1,5-IP8 is a signaling molecule that regulates phosphate and polyphosphate homeostasis in the fission yeast Schizosaccharomyces pombe. 1,5-IP8 levels are dictated by a balance between the Asp1 kinase domain that converts 5-IP7 to 1,5-IP8 and two pyrophosphatases—the Asp1 pyrophosphatase domain (histidine acid phosphatase family) and the Aps1 pyrophosphatase enzyme (Nudix family)—that hydrolyze the β-phosphates of 1,5-IP8. Here, we characterize S. pombe Siw14 (SpSiw14), a cysteinyl-phosphatase family member and a homolog of Saccharomyces cerevisiae Siw14, as a third fission yeast pyrophosphatase implicated in inositol pyrophosphate catabolism. We find that SpSiw14’s substrate repertoire embraces inorganic pyrophosphate, inorganic polyphosphate, and the inositol pyrophosphates 5-IP7, 1-IP7, and 1,5-IP8, in addition to the generic substrate p-nitrophenylphosphate. Genetic analyses revealed that (i) elimination of the SpSiw14 protein or inactivation of the SpSiw14 pyrophosphatase by the C189S mutation had no effect on S. pombe growth but was lethal in the absence of Aps1 and (ii) the synthetic lethality of siw14∆ aps1∆ depended on the synthesis of 1,5-IP8 by the Asp1 kinase. We conclude that SpSiw14 and Aps1 pyrophosphatases have essential but redundant functions in fission yeast, and that their synthetic lethality is a consequence of the toxic effects of too much 1,5-IP8. Suppression of siw14∆ aps1∆ lethality by loss-of-function mutations of components of the fission yeast 3′-processing/termination machinery fortifies the case for overzealous transcription termination as the basis for 1,5-IP8 toxicosis. IMPORTANCE The inositol pyrophosphate signaling molecule 1,5-IP8 modulates fission yeast phosphate homeostasis via its action as an agonist of RNA 3′-processing and transcription termination. Cellular 1,5-IP8 levels are determined by a balance between the activities of the inositol polyphosphate kinase Asp1 and several inositol pyrophosphatase enzymes. Here, we characterize Schizosaccharomyces pombe Siw14 (SpSiw14) as a cysteinyl-phosphatase-family pyrophosphatase enzyme capable of hydrolyzing the phosphoanhydride substrates inorganic pyrophosphate, inorganic polyphosphate, and inositol pyrophosphates 5-IP7, 1-IP7, and 1,5-IP8. Genetic analyses implicate SpSiw14 in 1,5-IP8 catabolism in vivo, insofar as: loss of SpSiw14 activity is lethal in the absence of the Nudix-type inositol pyrophosphatase enzyme Aps1; and siw14∆ aps1∆ lethality depends on synthesis of 1,5-IP8 by the Asp1 kinase. Suppression of siw14∆ aps1∆ lethality by loss-of-function mutations of 3′-processing/termination factors points to precocious transcription termination as the cause of 1,5-IP8 toxicosis.